A MODEL OF CHILDHOOD CURRICULUM MANAGEMENT FOR LEARNING TO DEVELOP THE HOLISTIC STUDENT EXPERIENCE PROVISION OF EDUCATIONAL INSTITUTIONS IN THE PRIMARY EDUCATION AREA NAKHON SAWAN PROVINCE ACCORDING TO IDDHIPA ̅DA IV - Phopromsri, Natthawadee; Gesthong , Thanee; Thosagai, Thanong (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims 1) to analyze the components of early childhood curriculum administration that provides learning experiences for the holistic development of children in educational institutions, 2) to create a model of early childhood curriculum administration that provides learning experiences for the holistic development of children in educational institutions based on the principle of the Four Iddhip da (Bases of accomplishment), and 3) to evaluate the model of early childhood curriculum administration that provides learning experiences for the holistic development of children in educational institutions based on the principle of the Four Iddhip da (Bases of accomplishment). The research methodology consisted of 3 steps: Step 1: Analysis of the components of early childhood curriculum administration that provides learning experiences for the holistic development of children in educational institutions from documents and interviews with 18 experts. Data were collected from a sample of 434 people. The statistics used were content analysis, frequency, percentage, standard deviation, and exploratory factor analysis. Step 2: Model creation by seminar with 9 experts. Data were analyzed using content analysis. And step 3: Model evaluation, data were collected from 30 experts. The statistics used were frequency, percentage, and standard deviation. The research results found that 1) Analysis of the components of early childhood curriculum administration that provided learning experiences for the holistic development of children in educational institutions, overall, it was at a high level which consisted of 4 components: Component 1: Early childhood curriculum administration factors; Component 2: Curriculum administration process; Component 3: Process of using the curriculum to organize learning experiences based on the concept of multiple intelligences for comprehensive child development; Component 4: Effectiveness of holistic student development. 2) The creation of an early childhood curriculum administration model that organized learning experiences for comprehensive child development of educational institutions in the primary educational area of Nakhon Sawan Province according to the principle of the Four Iddhip da. It consisted of 3 parts: Part 1: Introduction, including concepts and theories, objectives; Part 2: Content and guidelines for operation; Part 3: Conditions for success and the results of the model inspection were appropriate, the results of the evaluation of the appropriateness of the model manual were at a high level. And 3) The results of the evaluation of the early childhood curriculum administration model that organized learning experiences for comprehensive child development of educational institutions in the primary educational area of Nakhon Sawan Province according to the principle of the Four Iddhip da were at a high level in all 4 aspects: correctness, appropriateness, usefulness, and feasibility.